1995
DOI: 10.1074/jbc.270.46.27395
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Induces Activation of p38 MAP Kinase in Human Platelets

Abstract: Here we show that this kinase is identical with or closely related to p38 (the mammalian homolog of HOG1 from yeast), a recently discovered protein kinase typically activated by inflammatory cytokines and environmental stress. Further, we demonstrate that activation of this kinase by thrombin is transient (with maximal stimulation at 1 min), is accompanied by tyrosine phosphorylation, and precedes the activation of the ERK kinases. This is the first report to show that p38 kinase is activated by thrombin and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
159
2
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 19 publications
3
159
2
5
Order By: Relevance
“…Several authors have suggested that TRAP is only a partial agonist because it induces less expression of activated GPIIb-IIIa, fails to induce platelet prothrombinase activity, and causes weaker responses in terms of Ca ϩϩ mobilization, arachidonate production, and serotonin release. 8,9,28,29 Our studies do not fully support these concepts. In our hands, concentrations of thrombin and TRAP that induced similar aggregation responses in washed platelets resulted in nearly equivalent levels of phosphorylation at tyrosine residues of proteins present in whole platelet lysates.…”
Section: Discussioncontrasting
confidence: 48%
“…Several authors have suggested that TRAP is only a partial agonist because it induces less expression of activated GPIIb-IIIa, fails to induce platelet prothrombinase activity, and causes weaker responses in terms of Ca ϩϩ mobilization, arachidonate production, and serotonin release. 8,9,28,29 Our studies do not fully support these concepts. In our hands, concentrations of thrombin and TRAP that induced similar aggregation responses in washed platelets resulted in nearly equivalent levels of phosphorylation at tyrosine residues of proteins present in whole platelet lysates.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast, column fractions from thrombin-stimulated platelet lysates containing a prolinedirected kinase different from p42Ip44 MAP kinase phosphorylated recombinant cytosolic PLA, but not [Ala505]cytosolic PLA, [ll]. These fractions were analysed and contained p38 MAP kinase [15]. Recently, we reported that SB 203580 partially inhibits phosphorylation of cytosolic PLA, by thrombin [36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 15] showed activation of the 38-kDa MAP kinase in thrombinstimulated platelets and suggested that this kinase may phosphorylate cytosolic PLA,.…”
mentioning
confidence: 99%
“…Early experiments demonstrated that Src, Fyn or Yes could be activated by a host of GPCRs, including the lysophosphatidic acid (LPA), a2A adrenergic, M1 muscarinic, M2 muscarinic, a-thrombin, endothelin, angiotensin II, bombesin, bradykinin, and V2 vasopressin receptors (Simonson and Herman, 1993;Chen et al, 1994;Ishida et al, 1995;Kramer et al, 1995;Linseman et al, 1995;Ptasznik et al, 1995;Luttrell et al, 1996;Rodriguez-Fernandez and Rozengurt, 1996;Schieffer et al, 1996;Simonson et al, 1996). From the outset, there was evidence for heterogeneity in the mechanisms underlying GPCR control of Src activity.…”
Section: Gpcr Activation Of Src Family Kinases: When Worlds Collidementioning
confidence: 99%